2011
DOI: 10.1186/2191-219x-1-11
|View full text |Cite
|
Sign up to set email alerts
|

Imaging technologies for preclinical models of bone and joint disorders

Abstract: Preclinical models for musculoskeletal disorders are critical for understanding the pathogenesis of bone and joint disorders in humans and the development of effective therapies. The assessment of these models primarily relies on morphological analysis which remains time consuming and costly, requiring large numbers of animals to be tested through different stages of the disease. The implementation of preclinical imaging represents a keystone in the refinement of animal models allowing longitudinal studies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 59 publications
1
38
0
1
Order By: Relevance
“…We demonstrated that in the murine meniscectomy model of OA, calcium-containing crystal deposits were formed in the articular space prior to cartilage degradation (see online supplementary figure S1). These crystal deposits were previously identified as hypertrophic calcification,36 ectopic bone,37 mineralised area38 and heterotopic cartilage,39 but their chemical characterisation and their role in OA had never been determined. Starting from 1 month after OA induction, microCT-scan revealed multiple deposits within the joint, detached from bone, so that they could not be considered as osteophytes.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that in the murine meniscectomy model of OA, calcium-containing crystal deposits were formed in the articular space prior to cartilage degradation (see online supplementary figure S1). These crystal deposits were previously identified as hypertrophic calcification,36 ectopic bone,37 mineralised area38 and heterotopic cartilage,39 but their chemical characterisation and their role in OA had never been determined. Starting from 1 month after OA induction, microCT-scan revealed multiple deposits within the joint, detached from bone, so that they could not be considered as osteophytes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, confocal microscopy provided 90% power to detect a 30% difference in superficial chondrocyte density using 4 specimens per group for the femoral head, humeral head, and lateral femoral condyle and 6 specimens per group for the medial femoral condyle (Supplemental Table 3). At present, the confocal imaging method is limited to ex vivo analyses of cartilage structure, a limitation shared with other highresolution imaging techniques such as μCT and μMRI (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…This provides the ability of acquiring (almost) simultaneous in vivo images of highly resolved anatomy and accurately measured physiology in a noninvasive manner in animal models, clinical research, or diagnostics. This approach enables the explicit localization as well as the quantification of metabolic activity in target tissues [1, 2]. Nanoparticles embody unique imaging possibilities.…”
Section: Introductionmentioning
confidence: 99%